High risk medical transfer. Pre and interhospital assistance of the chest trauma - di Leoni, Francisco (Cirugía del Uruguay, 1990)
The application of scientific criteria in the management prehospital of the chest trauma patient and the multiple trauma patient severe in general, it is dated relatively recent.